Laminate and packaging bag

The laminate, featuring a biomass-rich sealant layer and enhanced laminate strength, addresses the environmental and performance challenges of packaging bags by providing improved tearability and impact resistance while reducing environmental impact.

JP2025071119AInactive Publication Date: 2025-05-02DAI NIPPON PRINTING CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2025020836
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-05-02
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Packaging bags require materials that reduce environmental impact, enhance impact resistance, and improve tearability, while current laminates using fossil fuel-derived polyethylene have significant environmental drawbacks.

Method used

A laminate comprising a substrate layer, a barrier layer, an adhesive layer, and a sealant layer with polyethylene as the main component, where the sealant layer includes ethylene-1-butene and ethylene-1-octene copolymers, with a biomass content of 5% or more, and a laminate strength of 5.0N or more between the sealant layer and adjacent layers.

Benefits of technology

The laminate achieves excellent environmental impact reduction, impact resistance, and tearability, making it suitable for packaging bags that require ease of opening and resistance to external and internal impacts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025071119000001_ABST
    Figure 2025071119000001_ABST
Patent Text Reader

Abstract

To provide a laminate that is excellent in environmental load reduction property as well as excellent in impact resistance and tear resistance.SOLUTION: A laminate comprises, in this order: a substrate layer, a barrier layer, an adhesion layer, and a sealant layer containing polyethylene as a main component. The barrier layer includes a metal foil. The sealant layer comprises, in this order: a laminate layer, an intermediate layer, and a sealing layer. The sealant layer contains an ethylene-1-butene copolymer and an ethylene-1-octene copolymer. A content of the ethylene-1-octene copolymer in the sealant layer is 1 mass% or more and 30 mass% or less. A biomass degree of the sealant layer is 5% or more. The sealant layer is adjacent to the adhesion layer. A laminate strength between the sealant layer and a layer adjacent to the sealant layer via the adhesion layer is 5.0 N or more at a width of 15 mm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate and a packaging bag. [Background technology]

[0002] Conventionally, packaging bags have been used to fill and package contents such as food, medicines, chemicals, and cosmetics. The laminate constituting the packaging bag includes a base layer such as a stretched film and a sealant layer having sealing properties. The packaging bag is manufactured by heat-sealing the sealant layer of the laminate.

[0003] In recent years, with the growing demand for the creation of a recycling-oriented society, there is a desire to move away from fossil fuels in the materials field, just as there is in energy, and the use of biomass has attracted attention. Biomass is an organic compound that is photosynthesized from carbon dioxide and water, and by using it, it becomes carbon dioxide and water again, making it a so-called carbon-neutral renewable energy. Recently, the practical application of biomass plastics made from these biomass raw materials has progressed rapidly, and attempts are being made to produce various resins from biomass raw materials.

[0004] As a biomass-derived resin, polylactic acid (PLA), which is produced via lactic acid fermentation, was the first to be commercially produced, but since its performance as a plastic differs significantly from current general-purpose plastics, including its biodegradability, there are limitations to its product applications and manufacturing methods, and it has not yet become widely used.In addition, a life cycle assessment (LCA) is being conducted on PLA, and discussions are being held on the energy consumption during PLA production and its equivalence when replacing general-purpose plastics.

[0005] Here, various types of polymers such as polyethylene, polypropylene, polyvinyl chloride, polystyrene, and polyester are used as general-purpose plastics. In particular, polyethylene is molded into films, sheets, bottles, etc. and used for various purposes such as packaging materials, and is used in large quantities around the world, so using conventional polyethylene derived from fossil fuels places a large burden on the environment. Therefore, it is desirable to use raw materials derived from biomass in the production of polyethylene to reduce the amount of fossil fuels used. For example, research has been conducted to date on the production of ethylene and butylene, which are raw materials for polyolefin resins, from renewable natural raw materials (see Patent Document 1). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Special Publication No. 2011-506628 Summary of the Invention [Problem to be solved by the invention]

[0007] It is desirable to use biomass-derived raw materials in laminates used in packaging bags to reduce the amount of fossil fuel used and the environmental impact. Packaging bags are required to have tearability that allows them to be easily opened by hand, and impact resistance that prevents them from being easily broken by external and internal impacts, and laminates used in packaging bags are also required to have good impact resistance and tearability.

[0008] The present invention has been made in view of the above-mentioned points, and an object of the present invention is to provide a laminate which is excellent in reducing the environmental load, and is also excellent in impact resistance and tear resistance. An object of the present invention is to provide a packaging bag including the laminate. [Means for solving the problem]

[0009] The present invention provides a laminate comprising, in this order, a base layer, a barrier layer, an adhesive layer, and a sealant layer containing polyethylene as a main component, the barrier layer comprises a metal foil; The sealant layer includes a laminate layer, an intermediate layer, and a seal layer in this order; the sealant layer comprises an ethylene-1-butene copolymer and an ethylene-1-octene copolymer; The content of the ethylene-1-octene copolymer in the sealant layer is 1% by mass or more and 30% by mass or less, The biomass content of the sealant layer is 5% or more; the sealant layer is adjacent to the adhesive layer; The laminate has a lamination strength between the sealant layer and the layer adjacent to the sealant layer via the adhesive layer of 5.0 N or more in a width of 15 mm.

[0010] In the laminate according to the present invention, the sealant layer may comprise biomass polyethylene.

[0011] In the laminate according to the present invention, the sealant layer may further comprise high pressure low density polyethylene.

[0012] In the laminate according to the present invention, the adhesive layer may be an adhesive layer.

[0013] The laminate according to the present invention may further comprise a support layer located between the base layer and the adhesive layer.

[0014] In the laminate according to the present invention, the base layer may be a stretched film.

[0015] The present invention is a packaging bag comprising the laminate. Effect of the Invention

[0016] According to the present invention, it is possible to provide a laminate which is excellent in reducing the environmental load and is also excellent in impact resistance and tear resistance. According to the present invention, a packaging bag including the laminate can be provided. [Brief description of the drawings]

[0017] [Figure 1] 1 is a schematic cross-sectional view showing one embodiment of a laminate according to the present invention. [Diagram 2] 1 is a schematic cross-sectional view showing one embodiment of a laminate according to the present invention. [Diagram 3] 1 is a schematic cross-sectional view showing one embodiment of a laminate according to the present invention. [Figure 4] FIG. 2 is a schematic diagram showing a method for measuring laminate strength. [Diagram 5] FIG. 2 is a schematic diagram showing a method for measuring laminate strength. [Figure 6] FIG. 13 is a diagram showing the measurement results of laminate strength. [Figure 7] FIG. 2 is a schematic diagram showing a method for measuring seal strength. [Figure 8] FIG. 2 is a schematic diagram showing an example of a method for measuring puncture strength. [Figure 9] 1 is a schematic diagram showing one embodiment of a packaging bag according to the present invention. [Figure 10] 1 is a schematic diagram showing one embodiment of a packaging bag according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will be described in detail below with reference to the accompanying drawings, in which the scale and aspect ratios have been appropriately altered and exaggerated from those of the actual objects for the sake of illustration and ease of understanding.

[0019] In addition, terms used in this specification that specify shapes, geometric conditions, and the extent thereof, such as "orthogonal" and "same," as well as values ​​of length and angle, are not limited to their strict meanings, but are interpreted to include a range within which similar functions can be expected.

[0020] [Laminate] The laminate according to the present invention comprises, in this order, a base layer, an adhesive layer, and a sealant layer containing polyethylene as a main component. In the laminate, the sealant layer is adjacent to the adhesive layer. In one embodiment, the laminate may further comprise a support layer located between the substrate layer and the adhesive layer. In one embodiment, the laminate may include a barrier layer located between the substrate layer and the adhesive layer.

[0021] Hereinafter, one embodiment of the laminate according to the present invention will be described with reference to the drawings.

[0022] In one embodiment, the laminate 10 includes, in this order, a substrate layer 11, an adhesive layer 12, and a sealant layer 13, as shown in Figure 1. As shown in Figure 1, the sealant layer 13 is adjacent to the adhesive layer 12. As shown in Figure 1, the substrate layer 11 is adjacent to the adhesive layer 12.

[0023] In one embodiment, the laminate 10 includes, in this order, a base layer 11, a support layer 14, an adhesive layer 12, and a sealant layer 13, as shown in Figure 2. As shown in Figure 2, the sealant layer 13 is adjacent to the adhesive layer 12. As shown in Figure 2, the support layer 14 is adjacent to the adhesive layer 12.

[0024] In one embodiment, laminate 10 includes, in that order, substrate layer 11, barrier layer 15, adhesive layer 12, and sealant layer 13, as shown in Figure 3. As shown in Figure 3, sealant layer 13 is adjacent to adhesive layer 12. As shown in Figure 3, barrier layer 15 is adjacent to adhesive layer 12. If laminate 10 includes support layer 14, barrier layer 15 may be located between substrate layer 11 and support layer 14 and / or between support layer 14 and adhesive layer 12 (not shown).

[0025] In one embodiment, the laminate 10 may include a printed layer (not shown) provided on at least one surface of the base layer 11 and / or the support layer 14. In one embodiment, the adhesive layer 12 may further be provided between at least one selected from the group consisting of between the substrate layer 11 and the support layer 14, between the substrate layer 11 and the barrier layer 15, and between the support layer 14 and the barrier layer 15 (not shown).

[0026] The layer structures of the laminate 10 described above can be appropriately combined.

[0027] In the laminate according to the present invention, the laminate strength between the sealant layer and the layer adjacent to the sealant layer via the adhesive layer (hereinafter also referred to as "adjacent layer") is 5.0 N or more in a width of 15 mm. By making the laminate strength 5.0 N or more, a laminate with excellent tear resistance can be realized. The reason for this is believed to be as follows.

[0028] A sealant layer containing polyethylene as a main component has high elongation at break and is therefore excellent in stretchability. On the other hand, such a sealant layer is difficult to tear, and therefore the tearability of the laminate is reduced when it is used in a laminate. It is believed that the laminate according to the present invention has improved tearability because the sealant layer is torn together with the adjacent layer when the adjacent layer is torn by improving the laminate strength between the sealant layer and the adjacent layer. In addition, although the mechanism is not clear at present, it is clear from the results of the examples and comparative examples described below that a laminate with remarkably excellent tearability can be realized by setting the laminate strength between the sealant layer and the adjacent layer to 5.0 N or more at a width of 15 mm.

[0029] In this specification, the laminate strength between the sealant layer and the adjacent layer is measured in accordance with JIS Z1707:2019. For example, a Tensilon universal material testing machine RTC-1530 manufactured by Orientec Co., Ltd. can be used as the measuring instrument. In this specification, unless otherwise specified, the environment during measurement of the laminate strength is a temperature of 23°C and a relative humidity of 90% RH.

[0030] Specifically, first, a laminate is cut out, and a strip-shaped test piece 20 is prepared by peeling off the sealant layer 21 and the adjacent layer 22 by 15 mm in the long side direction as shown in FIG. 4. The width of the test piece 20 is 15 mm. Then, as shown in FIG. 5, the already peeled parts of the sealant layer 21 and the adjacent layer 22 are respectively held by the grips 23 of the measuring device. The grips 23 are pulled at a speed of 50 mm / min in opposite directions perpendicular to the surface direction of the part where the sealant layer 21 and the adjacent layer 22 are still laminated, and the average value of the tensile stress F in the stable region is measured. The interval S1 between the grips 23 when the pulling starts is 30 mm, and the interval S1 between the grips 23 when the pulling ends is 60 mm. FIG. 6 is a diagram showing the change in the tensile stress F with respect to the interval S1 between the grips 23. As shown in Fig. 6, the change in tensile stress F with respect to the spacing S1 passes through a first region R1 and enters a second region R2 (stable region) where the rate of change is smaller than that of the first region R1. The average value of the tensile stress F in the stable region is measured for the five test pieces, and this average value is taken as the laminate strength.

[0031] The laminate strength between the sealant layer and the adjacent layer is preferably 6.0 N or more, more preferably 7.5 N or more, per 15 mm width. On the other hand, the laminate strength between the sealant layer and the adjacent layer is, for example, 30 N or less, and may be 20 N or less, per 15 mm width.

[0032] Each layer that may be included in the laminate according to the present invention will now be described.

[0033] <Base material layer> The substrate layer is a layer having a function of supporting the laminate. For example, a paper substrate, a resin film, or a laminate thereof can be appropriately used as the substrate layer.

[0034] The paper base material may be one having printability, flex resistance, rigidity, stiffness, strength, etc., and may be any of a variety of papers such as kraft paper, roll paper, paperboard, and processed paper.

[0035] The resin film contains at least one resin material. Examples of resin materials contained in the resin film include polyesters such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), 1,4-polycyclohexylene dimethylene terephthalate, and terephthalic acid-cyclohexanedimethanol-ethylene glycol copolymers; polyamides such as nylon 6, nylon 6,6, and polymetaxylylene adipamide (MXD6); polyolefins such as polyethylene (PE), polypropylene (PP), and polymethylpentene; vinyl resins such as polyvinyl chloride, polyvinyl alcohol (PVA), polyvinyl acetate, vinyl chloride-vinyl acetate copolymers, polyvinyl butyral, and polyvinylpyrrolidone (PVP); (meth)acrylic resins such as polyacrylate, polymethacrylate, and polymethyl methacrylate; cellulose resins such as cellophane, cellulose acetate, nitrocellulose, cellulose acetate propionate (CAP), and cellulose acetate butyrate (CAB); styrene resins such as polystyrene (PS), and chlorinated resins thereof. Among these, the resin material contained in the resin film is preferably at least one selected from the group consisting of polyolefin, polyester, and polyamide, and more preferably at least one selected from the group consisting of polypropylene, polyethylene terephthalate, nylon 6, and nylon 6,6.

[0036] The resin film may be a stretched film or an unstretched film. From the viewpoint of strength, the resin film is preferably a uniaxially or biaxially stretched film.

[0037] The surface of the resin film may be subjected to a surface treatment. The method of the surface treatment is not particularly limited, and examples thereof include physical treatments such as corona treatment, flame treatment, ozone treatment, low-temperature plasma treatment using oxygen gas and / or nitrogen gas, and glow discharge treatment, and chemical treatments such as oxidation treatment using chemicals.

[0038] The thickness of the base layer is, for example, 5 μm or more, and may be 10 μm, whereas the thickness of the base layer is, for example, 200 μm or less, and may be 100 μm or less, or may be 50 μm or less.

[0039] <Sealant layer> In the laminate according to the present invention, the sealant layer contains polyethylene as a main component. Such a sealant layer has high breaking elongation and excellent extensibility. In this specification, the term "main component" refers to a component that is contained in an amount of 50% by mass or more. From the viewpoint of stretchability, the content of polyethylene in the sealant layer is preferably 70% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, based on the entire sealant layer.

[0040] In this specification, polyethylene includes ethylene homopolymers and copolymers of ethylene and α-olefins (hereinafter also referred to as ethylene-α-olefin copolymers). The content of α-olefin units in the ethylene-α-olefin copolymers is, for example, 10 mol% or less, and may be 5 mol% or less.

[0041] Examples of the homopolymer of ethylene include high density polyethylene (HDPE), medium density polyethylene (MDPE), and high pressure low density polyethylene (LDPE). In this specification, high density polyethylene means polyethylene having a density of 0.942 g / cm 3 Medium density polyethylene means polyethylene having a density of 0.930 g / cm or more. 3 More than 0.942g / cm 3 High-pressure low-density polyethylene means polyethylene having a density of less than 0.910 g / cm 3 More than 0.930g / cm 3 High-pressure low-density polyethylene refers to polyethylene having a density of less than 1,000 atm. High-pressure low-density polyethylene can be obtained, for example, by polymerizing ethylene under high pressure of 1,000 atm or more and less than 2,000 atm. In this specification, the density of resins, layers, films, etc. is measured in accordance with Method B (pycnometer method) or Method D (density gradient tube method) of JIS K7112:1999. Method B or Method D is selected appropriately depending on the shape and mass of the test piece to be measured. In Method D, the measurement temperature (liquid temperature) is 23°C.

[0042] The ethylene-α-olefin copolymer may also be called linear polyethylene. Linear polyethylene will now be described. Linear polyethylene is a copolymer of ethylene and an α-olefin polymerized using a multi-site catalyst such as a Ziegler-Natta catalyst or a single-site catalyst such as a metallocene catalyst. It is therefore distinguished from an ethylene homopolymer. The α-olefins that serve as monomers for linear polyethylene have 3 or more carbon atoms, such as propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-nonene, 4-methylpentene, 3,3-dimethylbutene, and mixtures thereof. 0.930g / cm 3 Linear polyethylene having a density less than 1000 nm may be referred to as linear low density polyethylene (LLDPE).

[0043] The single-site catalyst is a catalyst capable of forming a uniform active species, and is usually prepared by contacting a metallocene transition metal compound or a nonmetallocene transition metal compound with an activation cocatalyst. Compared with a multi-site catalyst, a single-site catalyst has a uniform active site structure, and therefore can polymerize a polymer having a high molecular weight and a highly uniform structure. Particularly preferred examples of the single-site catalyst include metallocene catalysts. The metallocene catalyst is a catalyst that includes a transition metal compound of Group IV of the periodic table containing a ligand having a cyclopentadienyl skeleton, a cocatalyst, and if necessary, an organometallic compound and each catalyst component of a carrier.

[0044] In the above-mentioned transition metal compound of Group IV of the periodic table containing a ligand having a cyclopentadienyl skeleton, the cyclopentadienyl skeleton is a cyclopentadienyl group, a substituted cyclopentadienyl group, etc. Examples of the substituted cyclopentadienyl group include those having at least one substituent selected from a hydrocarbon group having 1 to 30 carbon atoms, a silyl group, a silyl-substituted alkyl group, a silyl-substituted aryl group, a cyano group, a cyanoalkyl group, a cyanoaryl group, a halogen group, a haloalkyl group, a halosilyl group, etc. The substituted cyclopentadienyl group may have two or more substituents, and the substituents may be bonded to each other to form a ring, such as an indenyl ring, a fluorenyl ring, an azulenyl ring, or a hydrogenated product thereof. The rings formed by bonding the substituents to each other may further have substituents.

[0045] In the transition metal compound of Group IV of the periodic table containing a ligand having a cyclopentadienyl skeleton, the transition metal may be zirconium, titanium, hafnium, etc., and is particularly preferably zirconium and / or hafnium. The transition metal compound preferably has two ligands having a cyclopentadienyl skeleton, and each ligand having a cyclopentadienyl skeleton is bonded to each other by a bridging group. Examples of the bridging group include an alkylene group having 1 to 4 carbon atoms, a silylene group, a substituted silylene group such as a dialkylsilylene group or a diarylsilylene group, and a substituted germylene group such as a dialkylgermylene group or a diarylgermylene group. The bridging group is preferably a substituted silylene group.

[0046] In the transition metal compound of Group IV of the periodic table, examples of the ligand other than the ligand having a cyclopentadienyl skeleton include hydrogen, hydrocarbon groups having 1 to 20 carbon atoms (such as alkyl groups, alkenyl groups, aryl groups, alkylaryl groups, aralkyl groups, and polyenyl groups), halogens, metaalkyl groups, and metaaryl groups.

[0047] The above-mentioned compounds of transition metals of Group IV of the periodic table containing a ligand having a cyclopentadienyl skeleton can be used as the catalyst component either alone or in combination of two or more kinds.

[0048] The co-catalyst refers to a catalyst that can effectively use the above-mentioned transition metal compound of Group IV of the periodic table as a polymerization catalyst or balance the ionic charge in a catalytically activated state. Examples of the co-catalyst include benzene-soluble aluminoxanes of organoaluminum oxy compounds and benzene-insoluble organoaluminum oxy compounds, ion-exchangeable layered silicates, boron compounds, ionic compounds consisting of cations containing or not containing active hydrogen groups and non-coordinating anions, lanthanoid salts such as lanthanum oxide, tin oxide, and phenoxy compounds containing fluoro groups.

[0049] The transition metal compound of Group IV of the periodic table containing a ligand having a cyclopentadienyl skeleton may be used supported on an inorganic or organic carrier, preferably an inorganic or organic porous oxide, and specific examples of the carrier include ion-exchangeable layered silicates such as montmorillonite, SiO2, Al2O3, MgO, ZrO2, TiO2, B2O3, CaO, ZnO, BaO, ThO2, and mixtures thereof.

[0050] Examples of organometallic compounds that may be used as necessary include organoaluminum compounds, organomagnesium compounds, organozinc compounds, etc. Of these, organoaluminum compounds are preferably used.

[0051] In the laminate according to the present invention, the sealant layer contains an ethylene-1-butene copolymer and an ethylene-1-octene copolymer. Among various linear polyethylenes, the ethylene-1-butene copolymer has excellent tearability, but is inferior to other linear polyethylenes in impact resistance. By containing an ethylene-1-butene copolymer having excellent tearability and an ethylene-1-octene copolymer having better impact resistance than the ethylene-1-butene copolymer in the sealant layer, a laminate having excellent impact resistance and tearability can be realized.

[0052] In the sealant layer, the content of the ethylene-1-butene copolymer is preferably greater than the content of the ethylene-1-octene copolymer. That is, when the content of the ethylene-1-butene copolymer is C4 and the content of the ethylene-1-octene copolymer is C8, it is preferable that C4 and C8 satisfy the relationship C4>C8. This can improve the impact resistance and tear resistance of the laminate. Note that C4 and C8 are based on mass.

[0053] The ratio of the content of the ethylene-1-octene copolymer to the content of the ethylene-1-butene copolymer in the sealant layer is preferably 0.05 or more, more preferably 0.1 or more, and even more preferably 0.3 or more, on a mass basis, while the ratio is preferably 0.99 or less, more preferably 0.9 or less, and even more preferably 0.6 or less, on a mass basis. By making the ratio 0.05 or more, the impact resistance of the laminate can be further improved. On the other hand, by making the ratio 0.99 or less, the tearability of the laminate can be further improved.

[0054] The content of the ethylene-1-butene copolymer in the sealant layer is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more, based on the entire sealant layer. By making the content of the ethylene-1-butene copolymer 5% by mass or more, the tearability of the laminate can be improved. On the other hand, the content of the ethylene-1-butene copolymer is, for example, 95% by mass or less, 92% by mass or less, 60% by mass or less, or 25% by mass or less, based on the entire sealant layer.

[0055] The content of the ethylene-1-octene copolymer in the sealant layer is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 8% by mass or more, based on the entire sealant layer, while the content of the ethylene-1-octene copolymer is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less, based on the entire sealant layer. By making the content of the ethylene-1-octene copolymer 1% by mass or more, the impact resistance of the laminate can be improved. On the other hand, by setting the content of the ethylene-1-octene copolymer to 30% by mass or less, the tearability of the laminate can be improved.

[0056] The ethylene-1-octene copolymer contained in the sealant layer preferably has a haze value of less than 20%, more preferably less than 17%. Although the reason for this is unclear, the use of an ethylene-1-octene copolymer having such a haze value can improve the tearability of the laminate. The haze value of the ethylene-1-octene copolymer is measured in accordance with ASTM D1003.

[0057] In one embodiment, the sealant layer may further include high-pressure low-density polyethylene (LDPE). When the sealant layer includes high-pressure low-density polyethylene, the tearability of the laminate can be further improved.

[0058] The content of the high-pressure low-density polyethylene is preferably 5% by mass or more, more preferably 10% by mass or more, based on the entire sealant layer. By making the content of the high-pressure low-density polyethylene 5% by mass or more, the tearability of the laminate can be further improved. On the other hand, the content of the high-pressure low-density polyethylene is, for example, 80% by mass or less, and may be 70% by mass or less, based on the entire sealant layer.

[0059] In the sealant layer, the ratio of the content of the ethylene-1-octene copolymer to the total content of the ethylene-1-butene copolymer and the high-pressure low-density polyethylene is preferably 0.05 or more, more preferably 0.1 or more, on a mass basis, while the ratio is preferably 0.5 or less, more preferably 0.3 or less, on a mass basis. By setting this ratio to 0.05 or more, the impact resistance of the sealant layer can be further improved. On the other hand, by setting the ratio to 0.5 or less, the tearability of the laminate can be further improved.

[0060] The sealant layer may contain high density polyethylene (HDPE) and / or medium density polyethylene (MDPE) as long as it does not impair the object of the present invention.

[0061] In one embodiment, the sealant layer may contain biomass polyethylene. When the sealant layer contains biomass polyethylene, the environmental load of the laminate can be reduced. The content of biomass polyethylene in the sealant layer is preferably 5% by mass or more, more preferably 50% by mass or more, and even more preferably 60% by mass or more, based on the entire sealant layer. On the other hand, the content of biomass polyethylene in the sealant layer may be, for example, 90% by mass or less, or 80% by mass or less, based on the entire sealant layer. As used herein, biomass polyethylene refers to a polymer of a monomer composition containing ethylene derived from biomass. The monomer composition may also contain ethylene derived from conventional fossil fuels. An example of a method for producing ethylene derived from biomass will be described below.

[0062] Biomass-derived ethylene can be produced using biomass-derived ethanol as a raw material. In particular, it is preferable to use biomass-derived fermented ethanol obtained from a plant raw material. The plant raw material is not particularly limited, and any conventionally known plant can be used. Examples of the plant raw material include corn, sugarcane, beet, and manioc.

[0063] Fermented ethanol derived from biomass refers to ethanol produced by contacting a culture solution containing a carbon source obtained from a plant raw material with an ethanol-producing microorganism or a product derived from the crushed microorganism, and then purifying the ethanol. Conventionally known methods such as distillation, membrane separation, and extraction can be applied to purify ethanol from the culture solution. For example, there is a method of adding benzene, cyclohexane, etc., and removing water by azeotropy or membrane separation.

[0064] In order to obtain the above ethylene, the ethanol may be further subjected to advanced purification at this stage, for example, so that the total amount of impurities in the ethanol is reduced to 1 ppm or less.

[0065] A catalyst is usually used when obtaining ethylene by the dehydration reaction of ethanol, but the catalyst is not particularly limited and any conventionally known catalyst can be used. From the viewpoint of the process, a fixed bed flow reaction is advantageous because it is easy to separate the catalyst from the product, and for example, γ-alumina is preferable.

[0066] This dehydration reaction is an endothermic reaction, and is usually carried out under heating conditions. As long as the reaction proceeds at a commercially useful reaction rate, the heating temperature is not limited, but is preferably 100° C. or higher, more preferably 250° C. or higher, and even more preferably 300° C. or higher. There is no particular upper limit, but from the viewpoint of energy balance and equipment, it is preferably 500° C. or lower, and more preferably 400° C. or lower.

[0067] In the dehydration reaction of ethanol, the yield of the reaction depends on the amount of water contained in the ethanol supplied as a raw material. In general, when performing a dehydration reaction, it is preferable to have no water in consideration of the efficiency of removing water. However, in the case of the dehydration reaction of ethanol using a solid catalyst, it has been found that the amount of other olefins, especially butene, produced tends to increase in the absence of water. It is presumed that this is because ethylene dimerization after dehydration cannot be suppressed without the presence of a small amount of water. The lower limit of the allowable water content is 0.1% by mass or more, and preferably 0.5% by mass or more. The upper limit is not particularly limited, but from the viewpoint of material balance and heat balance, it is preferably 50% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less.

[0068] By carrying out the dehydration reaction of ethanol in this manner, a mixture of ethylene, water, and a small amount of unreacted ethanol is obtained, but since ethylene is in a gaseous state at room temperature under approximately 5 MPa or less, water and ethanol can be removed from the mixture by gas-liquid separation to obtain ethylene. This can be done by a known method.

[0069] The ethylene obtained by the gas-liquid separation is further distilled. The distillation method, operation temperature, residence time, etc. are not particularly limited, except that the operation pressure at this time is normal pressure or higher.

[0070] When the raw material is biomass-derived ethanol, the obtained ethylene contains carbonyl compounds such as ketones, aldehydes, and esters, which are impurities mixed in during the ethanol fermentation process, as well as carbon dioxide gas, which is a decomposition product thereof, and nitrogen-containing compounds such as amines and amino acids, which are enzyme decomposition products and impurities, as well as ammonia, which is a decomposition product thereof. These impurities are desirably removed when ethylene is polymerized, since they may affect the polymerization catalyst, etc. On the other hand, although it is possible to reduce the content of these impurities contained in ethylene by a conventionally known purification method, it is difficult to completely remove the impurities from the viewpoints of cost and technology. Therefore, the ethylene obtained from biomass-derived ethanol contains a very small amount of impurities. As a result, biomass polyethylene, which is a polymer of a monomer composition containing biomass-derived ethylene, also contains a very small amount of impurities. In addition, biomass polyethylene also contains low molecular weight compounds such as unreacted monomers and oligomers, which are generated due to these impurities.

[0071] The inclusion of biomass polyethylene in the sealant layer according to the present invention can be determined by measuring the biomass content of the sealant layer. When the sealant layer contains biomass polyethylene, the biomass content of the sealant layer is greater than 0%.

[0072] Here, the biomass degree will be described. Carbon dioxide in the atmosphere contains a certain percentage of C14 (105.5 pMC), so it is known that the C14 content in plants that grow by absorbing carbon dioxide from the atmosphere, such as corn, is also about 105.5 pMC. It is also known that fossil fuels contain very little C14. Therefore, by measuring the percentage of C14 in the total carbon atoms, the percentage of carbon derived from biomass can be calculated. The "biomass degree" indicates the weight ratio of biomass-derived components. For example, in the case of polyethylene terephthalate, polyethylene terephthalate is a polymer of ethylene glycol containing two carbon atoms and terephthalic acid containing eight carbon atoms in a molar ratio of 1:1. Therefore, when only biomass-derived ethylene glycol is used, the weight ratio of biomass-derived components in the polyester is 31.25%, so the theoretical value of the biomass degree is 31.25%. Specifically, the mass of polyethylene terephthalate is 192, of which the mass derived from biomass-derived ethylene glycol is 60, so 60÷192×100=31.25. In addition, the weight ratio of biomass-derived components in the fossil fuel polyester produced using fossil fuel-derived ethylene glycol and fossil fuel-derived dicarboxylic acid is 0%, so the biomass degree of the fossil fuel polyester is 0%. Hereinafter, unless otherwise specified, the "biomass degree" indicates the weight ratio of biomass-derived components.

[0073] Theoretically, if only biomass-derived raw materials were used as the raw material for polyethylene, the concentration of biomass-derived ethylene would be 100%, and therefore the biomass content of biomass polyethylene would be 100%. The concentration of biomass-derived ethylene in fossil fuel polyethylene, which is produced only from fossil fuel-derived raw materials, is 0%. Therefore, the biomass content of fossil fuel-derived polyethylene is 0%.

[0074] In the laminate according to the present invention, the biomass degree of the sealant layer is 5% or more. This makes it possible to realize a laminate that is excellent in reducing the environmental load. The biomass degree of the sealant layer is preferably 50% or more, and more preferably 60% or more. On the other hand, the biomass degree of the sealant layer is, for example, 90% or less, and may be 80% or less.

[0075] The density of the sealant layer is preferably 0.900 g / cm 3 More preferably, it is 0.910 g / cm 3On the other hand, the density of the sealant layer is preferably 0.940 g / cm 3 More preferably, it is 0.925 g / cm 3 The following is the result. The density of the sealant layer is 0.900g / cm 3 By doing so, the tearability of the laminate can be improved. On the other hand, the density of the sealant layer is 0.940 g / cm 3 By setting the following, the sealing property of the laminate can be improved.

[0076] The thickness of the sealant layer is, for example, 20 μm or more, or may be 70 μm or more, or 100 μm or more, while the thickness of the sealant layer is, for example, 300 μm or less, or may be 200 μm or less, or may be 150 μm or less.

[0077] In one embodiment, the sealant layer may be a resin film having heat sealability (hereinafter, also referred to as a "sealant film"). By using a sealant film as the sealant layer, the process of forming the sealant layer becomes easier, and the productivity of the laminate can be improved.

[0078] The method for producing the sealant film is not particularly limited, and can be produced by a conventionally known method. The sealant film is preferably extrusion molded, and more preferably, the extrusion molding is performed by a T-die method or an inflation method. Hereinafter, an example of the method for producing the sealant film by the T-die method and the inflation method will be described.

[0079] In the T-die method, first, the materials constituting the sealant film are dried, and then supplied to a melt extruder heated to a temperature above the melting point (Tm) to Tm+100°C, where they are melted and extruded into a sheet from a T-die. The extruded sheet is then quenched and solidified on a rotating cooling drum or the like to form a sealant film. As the melt extruder, a single screw extruder, a twin screw extruder, a vent extruder, a tandem extruder, etc. can be used depending on the purpose.

[0080] In the inflation method, first, the material constituting the sealant film is dried, and then fed into a melt extruder heated to a temperature (Tm) to Tm+100°C above the melting point, where it is melted and extruded into a cylindrical shape through a ring die. At this time, air is fed into the cylindrical molten resin from below to expand the diameter of the cylinder to a predetermined size, and cooling air is fed from below to the outside of the cylinder. This expanded cylindrical body is called a bubble. Next, the bubble is folded into a film shape by a guide plate and a pinch roll, and wound up in a winding section. The folded film may be wound up as it is in a cylindrical shape, or both ends of the cylinder may be removed by a slitter or the like, cut into two films, and then each may be wound up. In this way, the sealant film can be formed. As the melt extruder, a single screw extruder, a twin screw extruder, a vent extruder, a tandem extruder, etc. can be used depending on the purpose.

[0081] When the sealant layer is a sealant film, the surface of the sealant film on the side of the adjacent layer may be subjected to a surface treatment. This can further improve the adhesion to the adjacent layer. Examples of the surface treatment method include the methods described above.

[0082] The sealant layer may contain one or more additives as long as the object of the present invention is not impaired. Examples of additives include plasticizers, UV stabilizers, color inhibitors, matting agents, deodorants, flame retardants, weather resistance agents, antistatic agents, friction reducers, slip agents, antiblocking agents, antioxidants, ion exchange agents, and color pigments. The sealant film preferably contains a slip agent and / or an antiblocking agent.

[0083] In one embodiment, the sealant layer may be a layer having a multi-layer configuration. Hereinafter, a sealant layer having a multi-layer structure will be described by taking as an example a sealant layer including a laminate layer, an intermediate layer, and a sealing layer in this order.

[0084] (Laminate layer) The laminate layer is a layer that constitutes one surface layer of the sealant layer, and is a layer that is located on the base layer side of the laminate.

[0085] In one embodiment, the laminate layer contains linear polyethylene. This improves the impact resistance of the laminate. In addition, the laminate layer contains linear polyethylene, which improves the adhesion between the laminate layer and the adjacent layer. The linear polyethylene may be linear low density polyethylene.

[0086] The linear polyethylene contained in the laminate layer may contain an ethylene-1-butene copolymer, or may contain at least one copolymer selected from the group consisting of an ethylene-1-butene copolymer and an ethylene-1-octene copolymer. The ethylene-1-octene copolymer may have the above-mentioned haze value.

[0087] From the viewpoint of the impact resistance of the laminate and adhesion to adjacent layers, the content of linear polyethylene in the laminate layer is preferably 50% by mass or more, more preferably 60% by mass, and even more preferably 70% by mass or more, based on the entire laminate layer. On the other hand, the content of linear polyethylene in the laminate layer is, for example, 95% by mass or less, or may be 90% by mass or less, or may be 85% by mass or less, based on the entire laminate layer.

[0088] The laminate layer may include high pressure low density polyethylene, which can improve the tearability of the laminate.

[0089] From the viewpoint of tearability of the laminate, the content of the high-pressure low-density polyethylene in the laminate layer is preferably 3% by mass or more, more preferably 8% by mass or more, and even more preferably 13% by mass or more, based on the entire laminate layer. On the other hand, the content of the high-pressure low-density polyethylene in the laminate layer is, for example, 45% by mass or less, or may be 35% by mass or less, or may be 25% by mass or less, based on the entire laminate layer.

[0090] The density of the laminate layer is preferably 0.900 g / cm 3 More preferably, it is 0.910 g / cm 3 On the other hand, the density of the laminate layer is preferably 0.940 g / cm 3 More preferably, it is 0.925 g / cm 3 The following is the result. The density of the laminate layer is 0.900g / cm 3 By doing so, the tearability of the laminate can be improved. On the other hand, the density of the laminate layer is 0.940 g / cm 3 By setting the above as follows, the adhesion to the adjacent layer can be improved.

[0091] The thickness of the laminate layer is, for example, 5 μm or more, or may be 10 μm or more, or may be 15 μm or more, whereas the thickness of the laminate layer is, for example, 70 μm or less, or may be 50 μm or less, or may be 35 μm or less.

[0092] The laminate layer may contain high density polyethylene (HDPE) and / or medium density polyethylene (MDPE) as long as the object of the present invention is not impaired.

[0093] In one embodiment, the laminate layer may contain biomass polyethylene, but the content of biomass polyethylene in the laminate layer is preferably less than 65% by mass relative to the entire laminate layer. This reduces the effect on the laminate strength between the sealant layer and the adjacent layer. Although the reason is unclear, as described above, biomass polyethylene contains impurities and low molecular weight compounds, and therefore, when the content of biomass polyethylene in the laminate layer increases, the content of impurities and low molecular weight compounds increases, which is thought to affect the laminate strength between the sealant layer and the adjacent layer. The content of biomass polyethylene in the laminate layer is more preferably less than 50% by mass, and even more preferably less than 30% by mass relative to the entire laminate layer. On the other hand, from the viewpoint of reducing the environmental load, the content of biomass polyethylene in the laminate layer is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more, based on the entire laminate layer.

[0094] The laminate layer may contain one or more additives as long as the object of the present invention is not impaired. Examples of additives include plasticizers, UV stabilizers, color inhibitors, matting agents, deodorants, flame retardants, weather resistance agents, antistatic agents, friction reducers, slip agents, antiblocking agents, antioxidants, ion exchange agents, and color pigments. The laminate layer preferably contains a slip agent.

[0095] (Sealing layer) The sealing layer is a layer that constitutes the other surface layer of the sealant layer, or a layer that constitutes one surface layer of the laminate or both surface layers of the laminate, and is a layer that is fused by heat.

[0096] In one embodiment, the seal layer contains linear polyethylene. This improves the impact resistance of the laminate. In addition, the seal layer contains linear polyethylene, which can lower the heat fusion temperature and improve the sealability of the sealant layer. The linear polyethylene may be linear low density polyethylene.

[0097] The linear polyethylene contained in the seal layer may contain an ethylene-1-octene copolymer, or may contain at least one copolymer selected from the group consisting of an ethylene-1-butene copolymer and an ethylene-1-octene copolymer. The ethylene-1-octene copolymer may have the above-mentioned haze value.

[0098] From the viewpoint of the impact resistance of the laminate and the sealability of the sealant layer, the content of linear polyethylene in the seal layer is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, based on the entire seal layer. On the other hand, the content of linear polyethylene in the seal layer is, for example, 95% by mass or less, or may be 90% by mass or less, or may be 85% by mass or less, based on the entire seal layer.

[0099] The sealing layer may comprise high pressure low density polyethylene, which can improve the tearability of the laminate.

[0100] From the viewpoint of tearability of the laminate, the content of the high-pressure low-density polyethylene in the seal layer is preferably 3% by mass or more, more preferably 8% by mass or more, and even more preferably 13% by mass or more, based on the entire seal layer. On the other hand, the content of the high-pressure low-density polyethylene in the laminate layer is, for example, 45% by mass or less, or may be 35% by mass or less, or may be 25% by mass or less, based on the entire seal layer.

[0101] The density of the sealing layer is preferably 0.900 g / cm 3 More preferably, it is 0.910 g / cm 3 On the other hand, the density of the sealing layer is preferably 0.940 g / cm 3 More preferably, it is 0.925 g / cm 3 The following is the result. The density of the sealing layer is 0.900g / cm 3 By doing so, the tearability of the laminate can be improved. On the other hand, the density of the seal layer is 0.940 g / cm 3 The sealing property of the sealant layer can be improved by the following.

[0102] The thickness of the sealing layer is, for example, 5 μm or more, or may be 10 μm or more, or may be 15 μm or more, while the thickness of the sealing layer is, for example, 70 μm or less, or may be 50 μm or less, or may be 35 μm or less.

[0103] The thickness ratio of the laminate layer to the seal layer is preferably 0.5 to 2, more preferably 0.8 to 1.2, and particularly preferably 0.9 to 1.1. By setting the thickness ratio in this range, the phenomenon in which the sealant layer warps, i.e., the so-called curl phenomenon, can be suppressed.

[0104] The sealing layer may contain high density polyethylene (HDPE) and / or medium density polyethylene (MDPE) without impairing the object of the present invention.

[0105] In one embodiment, the sealing layer may contain biomass polyethylene, but the content of biomass polyethylene in the sealing layer is preferably less than 65 mass%, more preferably less than 50 mass%, and even more preferably less than 30 mass%, of the entire sealing layer, from the viewpoint of the effect on sealing property that may be caused by impurities and low molecular weight compounds. On the other hand, from the viewpoint of reducing the environmental load, the content of biomass polyethylene in the seal layer is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more, based on the entire seal layer.

[0106] The sealing layer may contain one or more additives as long as the object of the present invention is not impaired. Examples of additives include plasticizers, UV stabilizers, color inhibitors, matting agents, deodorants, flame retardants, weather resistance agents, antistatic agents, friction reducers, slip agents, antiblocking agents, antioxidants, ion exchange agents, and color pigments. The sealing layer preferably contains a slip agent and / or an antiblocking agent.

[0107] (Middle class) The intermediate layer is a layer located between the seal layer and the laminate layer. The intermediate layer may be a single layer or multiple layers. When the intermediate layer is a multiple layer, the composition of each intermediate layer may be the same or different.

[0108] In one embodiment, the intermediate layer contains biomass polyethylene as a main component, which can improve the environmental load reduction of the laminate. From the viewpoint of reducing the environmental load, the content of biomass polyethylene in the intermediate layer is preferably 70% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, based on the entire intermediate layer.

[0109] The intermediate layer may comprise linear polyethylene and / or high pressure low density polyethylene. The linear polyethylene may be linear low density polyethylene. The intermediate layer preferably contains linear polyethylene from the viewpoint of the impact resistance of the sealant film, whereas the intermediate layer preferably contains high-pressure low-density polyethylene from the viewpoint of the tearability of the sealant film.

[0110] In the intermediate layer, the biomass polyethylene is preferably linear polyethylene and high-pressure low-density polyethylene.

[0111] The density of the intermediate layer is preferably 0.900 g / cm 3 More preferably, it is 0.910 g / cm 3 On the other hand, the density of the intermediate layer is preferably 0.940 g / cm 3 More preferably, it is 0.925 g / cm 3 The following is the result. The density of the sealing layer is 0.900g / cm 3 By doing so, the tearability of the laminate can be improved. On the other hand, the density of the seal layer is 0.940 g / cm 3 The impact resistance of the sealant layer can be improved by the following.

[0112] The thickness of the intermediate layer is, for example, 10 μm or more, may be 50 μm or more, or may be 70 μm or more, while the thickness of the intermediate layer is 160 μm or less, may be 100 μm or less, or may be 80 μm or less.

[0113] The thickness of the intermediate layer is preferably greater than that of the laminate layer, which can suppress curling of the sealant layer. The ratio of the thickness of the intermediate layer to the thickness of the laminate layer is preferably 1 to 10, more preferably 2 to 5. The thickness of the intermediate layer is preferably thicker than that of the seal layer. This can suppress curling of the sealant layer. The ratio of the thickness of the intermediate layer to the thickness of the seal layer is preferably 1 to 10, more preferably 2 to 5.

[0114] The intermediate layer may contain high density polyethylene (HDPE) and / or medium density polyethylene (MDPE) as long as the object of the present invention is not impaired.

[0115] The intermediate layer may contain one or more additives as long as the object of the present invention is not impaired. Examples of additives include plasticizers, ultraviolet stabilizers, color inhibitors, matting agents, deodorants, flame retardants, weather resistance agents, antistatic agents, friction reducers, slip agents, antiblocking agents, antioxidants, ion exchange agents, and color pigments. The intermediate layer preferably contains a slip agent.

[0116] In one embodiment, the sealant layer may be a sealant film including an intermediate layer and a sealing layer in this order, ie, a multi-layer sealant film.

[0117] The method for producing the multi-layer sealant film is not particularly limited, and can be produced by a conventionally known method. The multi-layer sealant film is preferably co-extruded, and more preferably, the co-extrusion is performed by a T-die method or an inflation method. Hereinafter, an example of the method for producing the multi-layer sealant film by the T-die method or the inflation method will be described.

[0118] In the T-die method, the materials constituting each layer are first dried, and then fed into a melt extruder heated to a temperature above the melting point (Tm) to Tm+100°C, where they are melted and extruded into a sheet from the T-die. The extruded sheet is then quenched and solidified on a rotating cooling drum or the like to form a multilayer sealant film. As the melt extruder, a single screw extruder, a twin screw extruder, a vent extruder, a tandem extruder, etc. can be used depending on the purpose.

[0119] In the inflation method, the materials constituting each layer are first dried, and then fed into a melt extruder heated to a temperature (Tm) to Tm+100°C above the melting point, where they are melted and extruded into a cylindrical shape through an annular die. At this time, air is fed into the cylindrical molten resin from below to expand the diameter of the cylinder to a predetermined size, and cooling air is fed from below to the outside of the cylinder. This expanded cylindrical body is called a bubble. Next, the bubble is folded into a film shape by a guide plate and a pinch roll, and wound up in a winding section. The folded film may be wound up as it is in a cylindrical shape, or both ends of the cylinder may be removed by a slitter or the like, cut into two films, and then each may be wound up. This allows the formation of a multilayer sealant film. As the melt extruder, a single screw extruder, a twin screw extruder, a vent extruder, a tandem extruder, etc. can be used depending on the purpose.

[0120] <Adhesive layer> The adhesive layer is an adhesive layer or an adhesive resin layer formed for laminating two layers together. The adhesive layer is preferably an adhesive layer because it has good adhesion to various layers, particularly to a sealant layer.

[0121] The adhesive layer is a layer formed using at least one type of one-liquid or two-liquid curable or non-curable laminating adhesive. Therefore, the adhesive layer includes a laminating adhesive. Examples of laminating adhesives include vinyl-based, (meth)acrylic-based, polyamide-based, polyester-based, polyether-based, polyurethane-based, epoxy-based, and rubber-based solvent-based, water-based, or emulsion-based laminating adhesives. Examples of methods for coating the adhesive include a direct gravure roll coating method, a gravure roll coating method, a kiss coating method, a reverse roll coating method, a Fontaine method, and a transfer roll coating method. The coating amount is, for example, 0.1 g / m in a dry state. 2 More than 1g / m 2 On the other hand, the coating amount is, for example, 10 g / m2 in a dry state. 2 Less than 5 g / m 2 A lower rank would be fine too.

[0122] The adhesive resin layer contains at least one thermoplastic resin. Examples of the thermoplastic resin contained in the adhesive resin layer include high-pressure low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-ethyl acrylate copolymer, ethylene-methacrylic acid copolymer, ethylene-methyl methacrylate copolymer, ethylene-maleic acid copolymer, and ionomer resin. Examples of the thermoplastic resin contained in the adhesive resin layer include resins obtained by graft-polymerizing or copolymerizing unsaturated carboxylic acid, unsaturated carboxylic acid anhydride, and ester monomer to polyolefin, and resins obtained by graft-modifying maleic anhydride to polyolefin. The thermoplastic resin may be made of a material derived from a fossil fuel, a material derived from biomass, or a combination of both.

[0123] <Support layer> The support layer is a layer that supports the laminate together with the base layer and improves the strength characteristics, durability, and the like of the laminate.

[0124] The support layer contains one or more resin materials. Examples of resin materials contained in the support layer include polyesters such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), 1,4-polycyclohexylene dimethylene terephthalate, and terephthalic acid-cyclohexanedimethanol-ethylene glycol copolymers; polyamides such as nylon 6, nylon 6,6, and polymetaxylylene adipamide (MXD6); polyolefins such as polyethylene (PE), polypropylene (PP), and polymethylpentene; vinyl resins such as polyvinyl chloride, polyvinyl alcohol (PVA), polyvinyl acetate, vinyl chloride-vinyl acetate copolymers, polyvinyl butyral, and polyvinylpyrrolidone (PVP); (meth)acrylic resins such as polyacrylate, polymethacrylate, and polymethyl methacrylate; cellulose resins such as cellophane, cellulose acetate, nitrocellulose, cellulose acetate propionate (CAP), and cellulose acetate butyrate (CAB); styrene resins such as polystyrene (PS), and chlorinated resins thereof. The support layer may be a resin film made of the above-mentioned resin material. From the viewpoint of strength, the resin film is preferably a film stretched in a uniaxial or biaxial direction.

[0125] The thickness of the support layer is, for example, 5 μm or more, and may be 10 μm, whereas the thickness of the support layer is, for example, 200 μm or less, and may be 100 μm or less, or may be 50 μm or less.

[0126] <Barrier layer> The barrier layer is a layer for imparting excellent gas barrier properties to the laminate. A laminate including a barrier layer has excellent barrier properties against gases such as oxygen and water vapor.

[0127] In one embodiment, the barrier layer may include a vapor-deposited film of an inorganic substance or an inorganic oxide, such as one or more inorganic substances such as silicon (Si), aluminum (Al), magnesium (Mg), calcium (Ca), potassium (K), tin (Sn), sodium (Na), boron (B), titanium (Ti), lead (Pb), zirconium (Zr), and yttrium (Y), or a vapor-deposited film of an inorganic oxide thereof. The vapor-deposited film can be formed on the surface of the base layer and / or support layer, etc. Examples of methods for forming the vapor-deposited film include known methods such as vacuum deposition, sputtering, and chemical vapor deposition.

[0128] The thickness of the evaporated film is, for example, 10 nm or more, and may be 20 nm or more, whereas the thickness of the evaporated film is, for example, 200 nm or less, and may be 100 nm or less.

[0129] In one embodiment, the barrier layer may include a gas barrier coating film located on the surface of the vapor-deposited film. When the barrier layer includes a gas barrier coating film, the gas barrier properties can be further improved.

[0130] The gas barrier coating film is represented by the general formula R 1 n M(OR 2 ) m (In the formula, R 1 , R 2 represents an organic group having 1 to 8 carbon atoms, M represents a metal atom, n represents an integer of 0 or more, m represents an integer of 1 or more, and n+m represents the atomic valence of M. The gas barrier composition contains at least one alkoxide represented by the formula (I) and the above-mentioned polyvinyl alcohol resin and / or ethylene-vinyl alcohol copolymer, and is further polycondensed by a sol-gel method in the presence of a sol-gel catalyst, an acid, water, and an organic solvent.

[0131] The above general formula R 1 n M(OR 2 ) mAs the alkoxide represented by the formula (I), at least one of a partial hydrolyzate of an alkoxide and a condensate of hydrolysis of an alkoxide can be used. As the partial hydrolyzate of an alkoxide, it is not necessary that all of the alkoxy groups are hydrolyzed, and one or more alkoxy groups may be hydrolyzed, or a mixture thereof. As the condensate of hydrolysis of an alkoxide, a dimer or more of a partially hydrolyzed alkoxide, preferably a dimer or more and a hexamer or less, is used.

[0132] The above general formula R 1 n M(OR 2 ) m In the alkoxide represented by the formula (I), silicon, zirconium, titanium, aluminum, and the like can be used as the metal atom represented by M. Preferred metals include, for example, silicon and titanium. The alkoxide may be used alone or in the form of a mixture of two or more different metal atoms in the same solution.

[0133] The above general formula R 1 n M(OR 2 ) m In the alkoxide represented by the formula: 1 Specific examples of the organic group represented by the general formula R include alkyl groups such as methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, sec-butyl, t-butyl, n-hexyl, and n-octyl. 1 n M(OR 2 ) m In the alkoxide represented by the formula: 2 Specific examples of the organic group represented by the formula (I) include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, a sec-butyl group, etc. These alkyl groups may be the same or different in the same molecule.

[0134] When preparing the gas barrier composition, for example, a silane coupling agent may be added. As the silane coupling agent, a known organoalkoxysilane containing an organic reactive group may be used. In particular, an organoalkoxysilane having an epoxy group may be preferably used. As the organoalkoxysilane having an epoxy group, for example, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, or β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane may be mentioned. The silane coupling agent may be used alone or in a mixture of two or more kinds.

[0135] In one embodiment, the barrier layer may include a metal foil. The metal foil is a foil containing one or more metal materials. Examples of the metal materials contained in the metal foil include aluminum, gold, silver, copper, stainless steel, titanium, and nickel. The metal foil can be laminated to the base layer and / or support layer, etc. via an adhesive layer.

[0136] <Print layer> The print layer is an image formed using a conventionally known pigment or dye. Examples of the image include characters, patterns, symbols, and combinations thereof. The print layer can be formed by a conventionally known method.

[0137] <Characteristics of laminate> The tear strength of the laminate is, for example, 0.1 N or more, and may be 0.5 N or more, in at least one direction. On the other hand, the tear strength of the laminate is, for example, 1.5 N or less, and may be 1.2 N or less, in at least one direction. In one embodiment, the tear strength of the laminate in the machine direction (MD) of the sealant layer is, for example, 0.1 N or more, and may be 0.5 N or more, while the tear strength of the laminate in the MD of the sealant layer is, for example, 1.5 N or less, and may be 1.2 N or less. In one embodiment, the tear strength of the laminate in the direction perpendicular to the machine direction (TD) of the sealant layer is, for example, 0.1 N or more, and may be 0.5 N or more, while the tear strength of the laminate in the TD of the sealant layer is, for example, 1.5 N or less, and may be 1.2 N or less. In this specification, the tear strength of the laminate is measured in accordance with the Elmendorf tear method of JIS K7128-2:1998. For example, an Elmendorf tear tester IM-701 manufactured by Tester Sangyo Co., Ltd. can be used as a measuring instrument. Measurement is performed on five test pieces, and the average value is taken as the tear strength. In this specification, unless otherwise specified, the environment during the measurement of tear strength is a temperature of 23°C and a relative humidity of 90% RH.

[0138] The seal strength of the laminate in a width of 15 mm is, for example, 10 N or more, or may be 20 N or more, or may be 30 N or more. On the other hand, the seal strength of the laminate in a width of 15 mm is, for example, 100 N or less, or may be 60 N or less. In this specification, the seal strength of the laminate is measured in accordance with JIS Z 1707:2019. For example, a Tensilon universal material testing machine RTC-1530 manufactured by Orientec Co., Ltd. can be used as a measuring instrument. In this specification, unless otherwise specified, the environment during the measurement of the seal strength is a temperature of 23°C and a relative humidity of 90% RH.

[0139] A method for measuring the seal strength will be described with reference to FIG. 7. First, the sealant layers of two laminates are heat-sealed to form a seal portion. Then, a portion including the seal portion is cut out to prepare a test piece 30 having a width of 15 mm and a length of 100 mm for measuring the seal strength. Next, as shown in FIG. 7, each of the unsealed portions of the test piece 30 is held by a gripper 31 of a measuring device. The length of the seal portion 32 is 15 mm. Next, the grippers 31 are pulled at a speed of 300 mm / min in opposite directions perpendicular to the surface direction of the seal portion 32 of the test piece 30, and the maximum value of the tensile stress is measured. Measurements are performed on five test pieces, and the average value of the maximum value of the tensile stress is taken as the seal strength. The interval S2 between the grippers 31 when pulling is started is 50 mm. The seal portion 32 of the test piece 30 was made by compressing the sealant layer of the two laminated sheets at 1 kgf / cm 2 The specimen is formed by heat sealing at 160°C for 1 second under a load of 1.

[0140] The piercing strength of the laminate is, for example, 10 N or more, or may be 15 N or more, or may be 18 N or more. On the other hand, the piercing strength of the laminate is, for example, 50 N or less, or may be 30 N or less. In one embodiment, the piercing strength of the laminate when pierced from the base layer side is, for example, 10 N or more, or may be 15 N or more, or may be 18 N or more. On the other hand, the piercing strength of the laminate when pierced from the base layer side is, for example, 50 N or less, or may be 30 N or less. In one embodiment, the puncture strength of the laminate when pierced from the sealant layer side is, for example, 10 N or more, and may be 15 N or more. On the other hand, the puncture strength of the laminate when pierced from the sealant layer side is, for example, 50 N or less, and may be 30 N or less. In this specification, the puncture strength of the laminate is measured in accordance with JIS Z1707:2019. For example, a Tensilon universal material testing machine RTC-1530 manufactured by Orientec Co., Ltd. can be used as a measuring instrument. In this specification, unless otherwise specified, the environment during the measurement of the puncture strength is a temperature of 23°C and a relative humidity of 90% RH.

[0141] The method for measuring the piercing strength will be described with reference to Fig. 8. As shown in Fig. 8, a semicircular needle 41 with a diameter of 1.0 mm and a tip radius of 0.5 mm is pierced into a fixed test piece 40 at a speed of 50 mm / min, and the maximum stress until the needle 41 penetrates the test piece 40 is measured. The maximum stress is measured for five test pieces, and the average value is taken as the piercing strength of the laminate.

[0142] <An example of layer structure of laminate> An example of the layer structure of the laminate according to the present invention is shown below. In the following example, the left side means the outside when the laminate is used as a packaging bag, and the right side means the inside (content side). In the following example, the symbol " / " means the boundary between each layer. (1) Base layer / printing layer / adhesive layer / sealant layer (2) Base layer / printing layer / adhesive layer / support layer / adhesive layer / sealant layer (3) Base layer / printing layer / adhesive layer / barrier layer / adhesive layer / sealant layer (4) Base layer / printing layer / adhesive layer / barrier layer / support layer / adhesive layer / sealant layer (5) Base layer / printing layer / adhesive layer / support layer / barrier layer / adhesive layer / sealant layer (6) Base layer / barrier layer / printing layer / adhesive layer / support layer / adhesive layer / sealant layer (7) Base layer / printing layer / adhesive layer / barrier layer / adhesive layer / support layer / adhesive layer / sealant layer (8) Base layer / printing layer / adhesive layer / support layer / adhesive layer / support layer / adhesive layer / sealant layer (9) Base layer / adhesive layer / sealant layer (10) Base layer / adhesive layer / support layer / adhesive layer / sealant layer (11) Base layer / adhesive layer / barrier layer / adhesive layer / sealant layer (12) Base layer / adhesive layer / barrier layer / support layer / adhesive layer / sealant layer (13) Base layer / adhesive layer / support layer / barrier layer / adhesive layer / sealant layer (14) Base layer / barrier layer / adhesive layer / support layer / adhesive layer / sealant layer (15) Base layer / adhesive layer / barrier layer / adhesive layer / support layer / adhesive layer / sealant layer (16) Base layer / adhesive layer / support layer / adhesive layer / support layer / adhesive layer / sealant layer

[0143] An example of a more specific layer structure of the laminate according to the present invention is shown below. In the following example, the left side means the outside when the laminate is used as a packaging bag, and the right side means the inside (contents side). In the following example, the symbol " / " means the boundary between each layer. In the following, "Ny" means nylon, "PE" means polyethylene, "PET" means polyethylene terephthalate, "AL" means aluminum, and "SiO" means silicon oxide. (1) Stretched Ny film / image / laminating adhesive / PE film (2) Stretched PET film / image / laminating adhesive / PE film (3) Stretched Ny film / image / laminating adhesive / stretched Ny film / laminating adhesive / PE film (4) Stretched Ny film / image / laminating adhesive / stretched PET film / laminating adhesive / PE film (5) Stretched PET film / image / laminating adhesive / stretched Ny film / laminating adhesive / PE film (6) Stretched PET film / image / laminating adhesive / stretched PET film / laminating adhesive / PE film (7) Stretched Ny film / image / laminating adhesive / AL foil / laminating adhesive / PE film (8) Stretched PET film / image / laminating adhesive / AL foil / laminating adhesive / PE film (9) Stretched Ny film / image / laminating adhesive / AL vapor deposition film / stretched PET film / laminating adhesive / PE film (10) Stretched Ny film / image / laminating adhesive / stretched PET film / AL vapor deposition film / laminating adhesive / PE film (11) Stretched PET film / SiO vapor deposition film / Image / Laminating adhesive / Stretched Ny film / Laminating adhesive / PE film (12) Stretched PET film / SiO vapor deposition film / gas barrier coating film / image / laminating adhesive / stretched Ny film / laminating adhesive / PE film (13) Stretched PET film / image / laminating adhesive / AL foil / laminating adhesive / stretched Ny film / laminating adhesive / PE film (14) Stretched PET film / image / laminating adhesive / AL foil / laminating adhesive / stretched PET film / laminating adhesive / PE film (15) Stretched PET film / image / laminating adhesive / stretched Ny film / laminating adhesive / stretched PET film / laminating adhesive / PE film (16) Stretched Ny film / laminating adhesive / PE film (17) Stretched PET film / laminating adhesive / PE film (18) Stretched Ny film / laminating adhesive / Stretched Ny film / laminating adhesive / PE film (19) Stretched Ny film / laminating adhesive / stretched PET film / laminating adhesive / PE film (20) Stretched PET film / laminating adhesive / stretched Ny film / laminating adhesive / PE film (21) Stretched PET film / laminating adhesive / Stretched PET film / laminating adhesive / PE film (22) Stretched Ny film / laminating adhesive / AL foil / laminating adhesive / PE film (23) Stretched PET film / laminating adhesive / AL foil / laminating adhesive / PE film (24) Stretched Ny film / laminating adhesive / AL vapor deposition film / stretched PET film / laminating adhesive / PE film (25) Stretched Ny film / laminating adhesive / stretched PET film / AL vapor deposition film / laminating adhesive / PE film (26) Stretched PET film / SiO vapor deposition film / laminating adhesive / stretched Ny film / laminating adhesive / PE film (27) Stretched PET film / SiO vapor deposition film / gas barrier coating film / laminating adhesive / stretched Ny film / laminating adhesive / PE film (28) Stretched PET film / laminating adhesive / AL foil / laminating adhesive / stretched Ny film / laminating adhesive / PE film (29) Stretched PET film / laminating adhesive / AL foil / laminating adhesive / stretched PET film / laminating adhesive / PE film (30) Stretched PET film / laminating adhesive / stretched Ny film / laminating adhesive / stretched PET film / laminating adhesive / PE film

[0144] [Method for producing laminate] The method for producing the laminate is not particularly limited, and the laminate can be produced by a conventionally known method such as a dry lamination method, a melt extrusion lamination method, or a sand lamination method.

[0145] [Packaging bag] The packaging bag according to the present invention includes the laminate according to the present invention. The laminate according to the present invention is excellent in reducing the environmental load and has excellent impact resistance and tear resistance, so that a packaging bag including the laminate is excellent in reducing the environmental load and has excellent impact resistance and tear resistance.

[0146] Fig. 9 is a schematic diagram showing one embodiment of a packaging bag according to the present invention. As shown in Fig. 9, packaging bag 50 includes body 51 and bottom 52. Body 51 is composed of two side sheets 53, and bottom 52 is composed of a bottom sheet 54. In packaging bag 50, side sheets 53 use laminate 10 according to the present invention. Therefore, packaging bag 50 is manufactured so that sealant layer 13 of laminate 10 is formed. In addition, the side sheets 53 and the bottom sheet 54 of the packaging bag 50 may be made of the same material or different materials.

[0147] The packaging bag 50 may include a pouring nozzle portion 55 as shown in Fig. 10. Moreover, the packaging bag 50 may include a curved portion 56 that is curved inward from the viewpoint of ease of opening as shown in Fig. 10. Furthermore, the packaging bag 50 may include a cutout portion 57 from the viewpoint of ease of opening as shown in Fig. 10. The cutout portion 57 can be formed by irradiating a laser beam or the like. 9 and 10, the hatched areas indicate the heat-sealed areas.

[0148] Since the packaging bag according to the present invention has excellent tearability, it is particularly preferable that the bag is provided with a cut-out portion 57 as shown in FIG.

[0149] The contents of the packaging bag are not particularly limited, but because of its excellent impact resistance, the packaging bag is particularly suitable for packaging liquids such as shampoo, conditioner, and detergent.

[0150] Other Aspects Another aspect of the present invention is a laminate comprising, in this order, a base layer, an adhesive layer, and a sealant layer containing polyethylene as a main component, the sealant layer comprises an ethylene-1-butene copolymer and an ethylene-1-octene copolymer; The biomass content of the sealant layer is 5% or more; the sealant layer is adjacent to the adhesive layer; The laminate has a lamination strength between the sealant layer and the layer adjacent to the sealant layer via the adhesive layer of 5.0 N or more in a width of 15 mm. In a laminate according to another aspect of the invention, the sealant layer may include biomass polyethylene. In the laminate according to another aspect of the present invention, the sealant layer may further comprise high pressure low density polyethylene. In the laminate according to another aspect of the present invention, the content of the ethylene-1-octene copolymer may be 30% by mass or less based on the entire sealant layer. In the laminate according to another aspect of the present invention, the adhesive layer may be an adhesive layer. The laminate according to another aspect of the present invention may further comprise a support layer located between the base layer and the adhesive layer. The laminate according to another aspect of the present invention may further comprise a barrier layer located between the substrate layer and the adhesive layer. In the laminate according to another aspect of the present invention, the base layer may be a stretched film. Another aspect of the present invention is a packaging bag comprising the laminate. EXAMPLES

[0151] Next, the present invention will be described more specifically with reference to examples. However, the present invention is not limited to the description of the following examples as long as it does not depart from the gist of the present invention.

[0152] The materials used in the examples are listed below. (1) Ethylene-1-butene copolymer (4LLDPE_A) ··· Density: 0.918g / cm 3 , MFR: 1.0g / 10min, Biomass content: 87%, Braskem, SLL118 (2) Ethylene-1-butene copolymer (4LLDPE_B) ··· Density: 0.918g / cm 3 , MFR: 4.0g / 10min, Biomass content: 0%, Ube Maruzen Polyethylene Co., Ltd., Yumerit 722FT (3) Ethylene-1-octene copolymer (8LLDPE)…density: 0.918g / cm 3 , MFR: 0.85g / 10min, Biomass ratio: 0%, Haze value: 15%, Dow, INNATE ST50 (4) High-pressure low-density polyethylene (LDPE_A) ··· Density: 0.923 g / cm 3 , MFR: 2.7g / 10min, Biomass content: 95%, Braskem, SEB853 (5) High-pressure low-density polyethylene (LDPE_B) ··· Density: 0.919 g / cm 3, MFR: 2.0g / 10min, Biomass ratio: 0%, Sumitomo Chemical Co., Ltd., G201-F(6) Masterbatch (MB_A)... Base material: polyethylene, Slip agent: erucic acid amide, Slip agent content: 2.0 mass%, Density: 0.921g / cm 3 , MFR: 5.4g / 10min, Ube Maruzen Polyethylene Co., Ltd., M425 (7) Masterbatch (MB_B) Base material: polyethylene, antiblocking agent: talc, slip agent: erucic acid amide, antiblocking agent content: 6.0 mass%, slip agent content: 1.5 mass%, density: 0.959 g / cm 3 , MFR: 2.5g / 10min, Ube Maruzen Polyethylene Co., Ltd., M615S

[0153] [Example 1A] A sealant film consisting of three layers was obtained by melting and co-extruding a mixture of 80 parts by mass of 4LLDPE_B, 19 parts by mass of LDPE_A, and 1 part by mass of MB_A as the laminate layer, a mixture of 99 parts by mass of LDPE_A and 1 part by mass of MB_A as the intermediate layer, and a mixture of 79 parts by mass of 8LLDPE, 19 parts by mass of LDPE_A, and 2 parts by mass of MB_B as the seal layer. The thickness of the sealant film is 130 μm. The thickness ratio of the laminate layer:intermediate layer:seal layer is 1:3:1.

[0154] Next, a biaxially oriented polyethylene terephthalate (PET) film having a thickness of 12 μm (E5100, manufactured by Toyobo Co., Ltd.) and a biaxially oriented nylon (Ny) film having a thickness of 15 μm (Bonyl-QC, manufactured by Kohjin Film & Chemicals Co., Ltd.) were prepared. The PET film and the Ny film were bonded together by a dry lamination method using a urethane adhesive (RU-77T / H-7, manufactured by Rock Paint Co., Ltd.).

[0155] Next, the Ny film and the sealant film were bonded together by dry lamination using a urethane adhesive (RU-77T / H-7, manufactured by Rock Paint Co., Ltd.) so that the laminate layer of the sealant film was located on the Ny film side.

[0156] As a result, a laminate was obtained that had, in this order, a PET film (base layer), a urethane adhesive (adhesive layer), a Ny film (support layer), a polyurethane adhesive (adhesive layer), and a sealant film (sealant layer). Note that the laminate layer of the sealant film was located on the Ny film side.

[0157] [Example 2A] A sealant film was obtained in the same manner as in Example 1A, except that a mixture of 50 parts by mass of 4LLDPE_B, 30 parts by mass of 8LLDPE, 19 parts by mass of LDPE_A, and 1 part by mass of MB_A was used as the lamination layer, and a mixture of 49 parts by mass of 4LLDPE_B, 30 parts by mass of 8LLDPE, 19 parts by mass of LDPE_A, and 2 parts by mass of MB_B was used as the seal layer. A laminate was obtained in the same manner as in Example 1A, except that this sealant film was used.

[0158] [Example 3A] A sealant film was obtained in the same manner as in Example 1A, except that a mixture of 79 parts by mass of 4LLDPE_B, 20 parts by mass of 8LLDPE, and 1 part by mass of MB_A was used as the lamination layer, a mixture of 99 parts by mass of 4LLDPE_A and 1 part by mass of MB_A was used as the intermediate layer, and a mixture of 79 parts by mass of 4LLDPE_B, 19 parts by mass of 8LLDPE, and 2 parts by mass of MB_B was used as the seal layer. A laminate was obtained in the same manner as in Example 1A, except that this sealant film was used.

[0159] [Comparative Example 1A] A sealant film was obtained in the same manner as in Example 1A, except that a mixture of 80 parts by mass of 8LLDPE, 19 parts by mass of LDPE_A, and 1 part by mass of MB_A was used as the laminating layer. A laminate was obtained in the same manner as in Example 1A, except that this sealant film was used.

[0160] [Comparative example 2A] A sealant film was obtained in the same manner as in Example 1A, except that a mixture of 79 parts by mass of 4LLDPE_B, 19 parts by mass of LDPE_A, and 2 parts by mass of MB_B was used as the sealing layer. A laminate was obtained in the same manner as in Example 1A, except that this sealant film was used.

[0161] [Comparative example 3A] A sealant film was obtained in the same manner as in Example 1A, except that a mixture of 99 parts by mass of 4LLDPE_B and 1 part by mass of MB_A was used as the lamination layer, a mixture of 99 parts by mass of 4LLDPE_A and 1 part by mass of MB_A was used as the intermediate layer, and a mixture of 98 parts by mass of 4LLDPE_B and 2 parts by mass of MB_B was used as the sealant layer. A laminate was obtained in the same manner as in Example 1A, except that this sealant film was used.

[0162] [Comparative example 4A] A sealant film was obtained in the same manner as in Example 1A, except that a mixture of 50 parts by mass of 4LLDPE_A, 30 parts by mass of 8LLDPE, 19 parts by mass of LDPE_A, and 1 part by mass of MB_A was used as the lamination layer, and a mixture of 50 parts by mass of 4LLDPE_B, 29 parts by mass of 8LLDPE, 19 parts by mass of LDPE_A, and 2 parts by mass of MB_B was used as the sealant layer. A laminate was obtained in the same manner as in Example 1A, except that this sealant film was used.

[0163] [Comparative example 5A] A mixture of 80 parts by mass of 4LLDPE_A, 19 parts by mass of 8LLDPE, and 1 part by mass of MB_A was used as the laminate layer, and a mixture of 28 parts by mass of 4LLDPE_B, 70 parts by mass of 8LLDPE, and 2 parts by mass of MB_B was used as the seal layer, which were melted and co-extruded into a film to obtain a sealant film composed of two layers. The thickness of the sealant film was 130 μm. The thickness ratio of the laminate layer:seal layer was 3:1. A laminate was obtained in the same manner as in Example 1A, except that this sealant film was used.

[0164] [Comparative Example 6A] A mixture of 70 parts by mass of 4LLDPE_A, 19 parts by mass of 8LLDPE, 10 parts by mass of LDPE_B, and 1 part by mass of MB_B was melted and extruded into a film to obtain a single-layer sealant film. The thickness of the sealant film was 130 μm. A laminate was obtained in the same manner as in Example 1A, except that this sealant film was used.

[0165] [Comparative Example 7A] A sealant film was obtained in the same manner as in Comparative Example 6A, except that a mixture of 39 parts by mass of 8LLDPE, 60 parts by mass of LDPE_A, and 1 part by mass of MB_B was used. A laminate was obtained in the same manner as in Example 1A, except that this sealant film was used.

[0166] [Comparative Example 8A] A sealant film was obtained in the same manner as in Comparative Example 6A, except that a mixture of 39 parts by mass of 4LLDPE_B, 60 parts by mass of LDPE_A, and 1 part by mass of MB_B was used. A laminate was obtained in the same manner as in Example 1A, except that this sealant film was used.

[0167] [Example 1B] A sealant was obtained in the same manner as in Example 1A, except that the thickness of the sealant film was 100 μm.

[0168] Next, a biaxially stretched polyethylene terephthalate (PET) film having a thickness of 12 μm (E5100, manufactured by Toyobo Co., Ltd.) and an aluminum foil having a thickness of 7 μm (8079 foil, manufactured by Toyo Aluminum Co., Ltd.) were prepared. The PET film and the aluminum foil were bonded together by a dry lamination method using a urethane adhesive (RU-77T / H-7, manufactured by Rock Paint Co., Ltd.).

[0169] Next, a biaxially oriented nylon (Ny) film having a thickness of 15 μm (Bonyl-QC, manufactured by Kohjin Film & Chemicals Co., Ltd.) was prepared. The aluminum foil and the Ny film were bonded together by a dry lamination method using a urethane adhesive (RU-77T / H-7, manufactured by Rock Paint Co., Ltd.).

[0170] Next, the Ny film and the sealant film were bonded together by dry lamination using a urethane adhesive (RU-77T / H-7, manufactured by Rock Paint Co., Ltd.) so that the laminate layer of the sealant film was located on the Ny film side.

[0171] As a result, a laminate was obtained that had, in this order, a PET film (base layer), a polyurethane adhesive (adhesive layer), an aluminum foil (barrier layer), a polyurethane adhesive (adhesive layer), a Ny film (support layer), a polyurethane adhesive (adhesive layer), and a sealant film (sealant layer). Note that the laminate layer of the sealant film was located on the Ny film side.

[0172] [Example 2B] A sealant was obtained in the same manner as in Example 2A, except that the thickness of the sealant film was 100 μm. A laminate was obtained in the same manner as in Example 1B, except that this sealant film was used.

[0173] [Example 3B] A sealant was obtained in the same manner as in Example 3A, except that the thickness of the sealant film was 100 μm. A laminate was obtained in the same manner as in Example 1B, except that this sealant film was used.

[0174] [Comparative example 1B] A sealant was obtained in the same manner as in Comparative Example 1A, except that the thickness of the sealant film was 100 μm. A laminate was obtained in the same manner as in Example 1B, except that this sealant film was used.

[0175] [Comparative Example 2B] A sealant was obtained in the same manner as in Comparative Example 2A, except that the thickness of the sealant film was 100 μm. A laminate was obtained in the same manner as in Example 1B, except that this sealant film was used.

[0176] [Comparative example 3B] A sealant was obtained in the same manner as in Comparative Example 3A, except that the thickness of the sealant film was 100 μm. A laminate was obtained in the same manner as in Example 1B, except that this sealant film was used.

[0177] [Comparative example 4B] A sealant was obtained in the same manner as in Comparative Example 4A, except that the thickness of the sealant film was 100 μm. A laminate was obtained in the same manner as in Example 1B, except that this sealant film was used.

[0178] [Comparative Example 5B] A sealant was obtained in the same manner as in Comparative Example 5A, except that the thickness of the sealant film was 100 μm. A laminate was obtained in the same manner as in Example 1B, except that this sealant film was used.

[0179] [Comparative Example 6B] A sealant was obtained in the same manner as in Comparative Example 6A, except that the thickness of the sealant film was 100 μm. A laminate was obtained in the same manner as in Example 1B, except that this sealant film was used.

[0180] [Comparative Example 7B] A sealant was obtained in the same manner as in Comparative Example 7A, except that the thickness of the sealant film was 100 μm. A laminate was obtained in the same manner as in Example 1B, except that this sealant film was used.

[0181] [Comparative Example 8B] A sealant was obtained in the same manner as in Comparative Example 8A, except that the thickness of the sealant film was 100 μm. A laminate was obtained in the same manner as in Example 1B, except that this sealant film was used.

[0182] Tables 1 and 2 show details of the sealant films (sealant layers) obtained in the examples and comparative examples.

[0183] [Table 1]

[0184] [Table 2]

[0185] <<Laminate strength measurement>> In the laminates of the examples and comparative examples, the laminate strength between the sealant layer and the adjacent layer was measured in accordance with JIS Z1707: 2019. The measuring instrument used was a Tensilon universal material testing machine RTC-1530 manufactured by Orientec Co., Ltd. In the laminates of the examples and comparative examples, the sealant layer was a sealant film, and the adjacent layer was a Ny film. Specifically, first, a laminate was cut out, and a strip-shaped test piece 20 was prepared by peeling off the sealant layer 21 and the adjacent layer 22 by 15 mm in the long side direction as shown in FIG. 4. The width of the test piece 20 was 15 mm. Then, as shown in FIG. 5, the already peeled parts of the sealant layer 21 and the adjacent layer 22 were gripped by the grips 23 of the measuring device. The grips 23 were pulled at a speed of 50 mm / min in opposite directions perpendicular to the surface direction of the part where the sealant layer 21 and the adjacent layer 22 are still laminated, and the average value of the tensile stress F in the stable region was measured. The interval S1 between the grips 23 when the pulling started was 30 mm, and the interval S1 between the grips 23 when the pulling ended was 60 mm. FIG. 6 is a diagram showing the change in the tensile stress F with respect to the interval S1 between the grips 23. As shown in Figure 6, the change in tensile stress F with respect to the spacing S1 passed through a first region R1 and entered a second region R2 (stable region) where the rate of change was smaller than that of the first region R1. The average value of tensile stress F in the stable region was measured for five test pieces, and this average value was taken as the laminate strength. The laminate strength was measured in an environment of a temperature of 23°C and a relative humidity of 90%RH. The measurement results are shown in Tables 3 and 4.

[0186] <<Tear strength measurement>> The tear strength of the laminates of the examples and comparative examples was measured in accordance with the Elmendorf tear method of JIS K7128-2:1998. The measuring device used was an Elmendorf tear tester IM-701 manufactured by Tester Sangyo Co., Ltd. Measurements were performed on five test pieces, and the average value was taken as the tear strength. The impact strength was measured in an environment of a temperature of 23°C and a relative humidity of 90%RH. The measurement results are shown in Tables 3 and 4.

[0187] <<Seal strength measurement>> The seal strength of the laminates of Examples 1A to 3A and Comparative Examples 1A to 8A was measured in accordance with JIS Z 1707: 2019. The measuring instrument used was a Tensilon universal material testing machine RTC-1530 manufactured by Orientec Co., Ltd. Specifically, first, the sealant layers of two laminates were heat-sealed to each other to form a seal portion. Then, a portion including the seal portion was cut out to prepare a test piece 30 having a width of 15 mm and a length of 100 mm for measuring the seal strength. Next, as shown in FIG. 7, each of the unsealed portions of the test piece 30 was held by a gripper 31 of a measuring device. The length of the seal portion 32 was set to 15 mm. Next, the grippers 31 were pulled at a speed of 300 mm / min in opposite directions in a direction perpendicular to the surface direction of the seal portion 32 of the test piece 30, and the maximum value of the tensile stress was measured. Measurements were performed on five test pieces, and the average value of the maximum value of the tensile stress was taken as the seal strength. The interval S2 between the grippers 31 when the pulling was started was set to 50 mm. The seal portion 32 of the test piece 30 was made by compressing the sealant layer of the two laminated sheets at 1 kgf / cm 2 The specimen was formed by heat fusion at 160° C. for 1 second under a load of 1.0 μm. The heat fusion temperature was changed to 130°C, 140°C, 150°C, 170°C, 180°C, 190°C, and 200°C, and the seal strength was measured in the same manner as above. The environment during the seal strength measurement was a temperature of 23°C and a relative humidity of 90%RH. The measurement results are shown in Table 3.

[0188] <<Measurement of puncture strength>> The puncture strength of the laminates of the examples and comparative examples was measured in accordance with JIS Z1707: 2019. The measuring instrument used was a Tensilon universal material testing machine RTC-1530 manufactured by Orientec Co., Ltd. Specifically, as shown in FIG. 8, a semicircular needle 41 having a diameter of 1.0 mm and a tip radius of 0.5 mm was pierced into a test piece 40 in a fixed state at a speed of 50 mm / min, and the maximum value of stress until the needle 41 penetrated the test piece 40 was measured. The maximum stress was measured for five test pieces, and the average value was taken as the piercing strength of the laminate. The piercing strength was measured when piercing from the base layer side and when piercing from the sealant layer side. The environment during the piercing strength measurement was a temperature of 23° C. and a relative humidity of 90% RH. The measurement results are shown in Tables 3 and 4.

[0189] <<Drop test>> The packaging bag 50 shown in FIG. 10 was produced using the laminates of Examples 1A to 3A and Comparative Examples 1A to 8A. Next, 320 mL of water was filled into the packaging bag 50. Next, the opening of the packaging bag 50 was heat-sealed to hermetically seal the packaging bag 50. The packaging bag 50 was dropped vertically from a height of 120 cm to the ground 10 times. This was performed on five packaging bags 50, and the tearing of the packaging bag 50 was confirmed. The same drop test was also performed in the horizontal direction to confirm the tearing of the packaging bag 50. The results are shown in Table 3. The drop test values ​​shown in Table 3 refer to the number of broken packaging bags 50. The vertical direction means a state in which the bottom 52 of the packaging bag 50 is facing downward, and the horizontal direction means a state in which the side sheets 53 constituting the body 51 of the packaging bag 50 face the ground. The same drop test as above was performed on the laminates of Examples 1B to 3B and Comparative Examples 1B to 8B with the amount of water filled set to 250 mL. The results are shown in Table 4. The drop test values ​​shown in Table 4 refer to the number of broken packaging bags 50.

[0190] [Table 3]

[0191] [Table 4]

[0192] <<Evaluation of environmental impact reduction>> The environmental load reducing properties of the laminates in the examples and comparative examples were evaluated based on the following evaluation criteria. The evaluation results are shown in Tables 5 and 6. · Good: The biomass content of the sealant layer is 5% or more. · No Good: The biomass content of the sealant layer is less than 5%.

[0193] <<Impact resistance evaluation>> The impact resistance of the laminates in the examples and comparative examples was evaluated based on the following evaluation criteria. The evaluation results are shown in Tables 5 and 6. · Good: None of the packaging bags 50 were broken in the vertical and horizontal drop tests. · No Good: At least one packaging bag 50 was broken in the vertical and horizontal drop tests.

[0194] <<Evaluation of tearability>> The tearability of the laminates in the examples and comparative examples was evaluated based on the following evaluation criteria. The evaluation results are shown in Tables 5 and 6. ·Good: The tear strength in both MD and TD is less than 1.5N. · No Good: The tear strength in MD or TD is 1.5N or more.

[0195] [Table 5]

[0196] [Table 6]

[0197] The laminate according to the present invention is excellent in reducing the environmental load, and is also excellent in impact resistance and tear resistance. [Explanation of symbols]

[0198] 10: Laminate 11: Base material layer 12: Adhesive layer 13: Sealant layer 14: Support layer 15: Barrier layer 20: Test piece 21: Sealant layer 22: Adjacent layer 23: Grasping tool 30: Test piece 31: Grip tool 32: Seal part 40: Test piece 41: Needle 50: Packaging bag 51: Torso 52: Bottom 53: Side sheet 54: Bottom sheet 55: Nozzle for pouring 56: Curved section 57: Cut-out section

Claims

1. A laminate comprising, in this order, a base layer, a barrier layer, an adhesive layer, and a sealant layer containing polyethylene as a main component, the barrier layer comprises a metal foil; The sealant layer includes a laminate layer, an intermediate layer, and a seal layer in this order; the sealant layer comprises an ethylene-1-butene copolymer and an ethylene-1-octene copolymer; The content of the ethylene-1-octene copolymer in the sealant layer is 1% by mass or more and 30% by mass or less, The biomass content of the sealant layer is 5% or more; the sealant layer is adjacent to the adhesive layer; A laminate having a laminate strength between the sealant layer and a layer adjacent to the sealant layer via the adhesive layer of 5.0 N or more in a width of 15 mm.

2. The laminate of claim 1 , wherein the sealant layer comprises biomass polyethylene.

3. 3. The laminate of claim 1 or 2, wherein the sealant layer further comprises high pressure low density polyethylene.

4. The laminate according to any one of claims 1 to 3, wherein the adhesive layer is an adhesive layer.

5. The laminate according to any one of claims 1 to 4, further comprising a support layer located between the base material layer and the adhesive layer.

6. The laminate according to any one of claims 1 to 5, wherein the base layer is a stretched film.

7. A packaging bag comprising the laminate according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Packaging material for liquid food using deposited film laminate

    JP2000301678A

  • Lid material and packaging container using the same

    JP2015231870A

  • Sealant film, and packaging material and packaging bag using the same

    JP2017105197A

  • Sealant film, and packaging material and packaging bag using the same

    JP2018047703A

  • Sealant film, and packaging material and packaging bag using the same

    JP2018052120A